Mexico : Detailed Assessment of Observance of International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report, 2012)
A detailed assessment on the observance of Mexico's compliance with International Organization of Securities Commissions objectives and principles of securities regulation is presented. The regimes governing the regulation of issuers, collective investment schemes, and secondary markets, and with respect to cooperation and information sharing, are extensive. The most significant issues regarding full implementation of the Principles fall under the Regulator Principles. Much of the activity on the Bolsa Mexicana de Valores comes from computer-driven program trading orders that are placed to take advantage of price asymmetries between markets.